Phosphorus Oxychloride Promoted Hydrogen Peroxide for Selective Oxidation of Thiols to Disulfides - Lakouraj, M.M.; Hasantabar, V. (Asian Journal of Chemistry, 2010)
Oxidation of aliphatic and aromatic thiols to the corresponding symmetric disulfides was achieved by using POCl3/H2O2. A new procedure for the oxidation of thiols to disulfides without any over oxidation has been reported. It is noteworthy that the reaction is clean and tolerates oxidatively sensitive functional groups.